Situational analysis of primary health care of children in Ukraine - Yu.G. Antipkin; О.P. Volosovets; V.F. Lapshin; R.V. Marushko; O.O. Dudina (Zaslavsky O.Yu., 2020)
Background. During the period of political and economic changes, prolonged war conflict in Ukraine, a number of medical and environmental problems have arose that pose a threat to the health of various groups of the population, especially children, whose health status is one of the major social problems in Ukraine. The purpose of the study was to conduct a retrospective analysis of the provision of primary medical care to the child population of Ukraine for the period of 1990-2018. Materials and methods. The article presents the data from a retrospective analysis of the provision of primary medical care to the child population in Ukraine for the period of 1990-2018 according to state and industry statistics. We have used methods of a systematic approach, statistical processing of the material, graphic images. Results. The analysis showed that changes in the primary care of children are due to the status of the demographic situation in the country and health care reforms. It was found that over the years of sovereignty, the availability of primary care of children (11.6 visits per 1 child per year) was preserved in Ukraine, as well as its preventive orientation, sufficient treatment coverage of children in day care facilities, complete pathology detection during preventive examinations, positive dynamics of breastfeeding of infants. Conclusions. In the context of healthcare reforms, the development and implementation of new medical and organizational technologies, on the one hand, and the shortage of pediatric specialists, on the other hand, a combined model of collaboration between family doctors and pediatricians is reasonable. Children's health care should be identified as a priority to ensure effective financing of this important area of medicine in order to increase attention to population reproduction and preserving the health of the generation that is born. On this direction, the development and implementation of the state action plan "Children's Health is a Start for a Lifetime" will make a significant contribution to improving the demographic situation in the country and the health of the child population.